Perancangan Aplikasi Kompresi File Gambar Menggunakan Algoritma Elias Omega Code - Puji Lestari; Surya Darma Nasution (Journal of Information System Research (JOSH), 2022)
The habit of collecting data makes the capacity of large storage space smaller, making it difficult for computer users to store large amounts of data or large data. One of the files that are large and usually collected by humans is image files, this takes up a lot of storage space. One solution to overcome this problem is to use a compression algorithm such as elias omega code so that the size of large image files becomes smaller. Elias Omega Code Algorithm is a compression algorithm with a lossless compression type, where the compression results can be returned as before without any bit loss. The purpose of using the elias omega algorithm is so that the image file that is saved becomes a small image file. The results obtained from building an image file compression application are that the image file size becomes smaller, with a compression ratio of 66.5%.